High-intensity, non-sport-specific strength and conditioning for Brazilian jiu-jitsu athletes: Theoretical and practical considerations. - Øvretveit, K. (Strength and Conditioning Journal, 2020)
Brazilian jiu-jitsu (BJJ) is a grappling-based combat sport with a growing recreational and professional athlete population. The sport is notoriously hard to master, which requires practitioners to maintain a high BJJ-specific training volume. High-intensity training is a well-established approach to rapid improvements in strength and endurance. Recent studies show that concomitant BJJ and high-intensity strength and conditioning training can improve several physical and physiological attributes. The present article briefly reviews literature pertaining to BJJ and its athletes and provides training recommendations based on high-intensity strength and conditioning concepts.